Husband Involvement in Birth Preparedness and Complication Readiness and Associated Factors in Selected Hospitals of Kaski - Ojha, Sujata; Lawot, Isabel; Poudel, Sharmila (Journal of Karnali Academy of Health Sciences, 2021)
Background: Men in patriarchal societies are decision makers and their involvement in maternal health enable adequate preparation and decision making during obstetric complications reducing 3 delays in women’s life. The objective of the study was to identify knowledge and practice of husband in birth preparedness and complication readiness. Methods: A descriptive cross-sectional research was used to assess the knowledge and practices of husbands of postnatal women two tertiary hospitals of Kaski district. Purposive sampling was adopted to select 384 respondents. Data was collected using semi-structured interviews. Descriptive (frequency, mean, standard deviation and percent) and inferential (chi-square test and logistic regression) statistics were used for data analysis. Results: The study found that knowledge of the respondents on Birth Preparedness and Complication Readiness was 59.1% and practice was 51.8%. Significant association was found between knowledge and practice of respondents. The factors associated with husband involvement were assessed using Andersen’s behavioral model. Age (p=.001), education (p=.001), residence (p=.001), parity (p=0.001), family type (p=0.001), mass media (p=.001), number of ANC visit conducted (p=.002) and history of obstetric complication (p=.001) were found to be statistically significant with knowledge. Factors contributing to practice of husband in Birth Preparedness, Complication Readiness were age, availability of transportation and health insurance. Conclusion: Based on these findings, the knowledge and practice of husband should be increased and more educational programs focusing on involvement in Birth Preparedness and Complication Readiness needs to be increased.